Cellular and molecular mechanisms of apoptosis in skeletal muscle atrophy - Voltarelli, F. A. [UNESP] (2007)
Apoptosis is necessary for maintaining the integrity of proliferative tissues, such as epithelial cells of the gastrointestinal and integumentary systems. The role of apoptosis in post-mitotic tissues, such as skeletal muscle, is less well defined, but several lines of evidence suggest that it occurs in both myofiber and other interstitial muscle cell types. Apoptosis of myonuclei likely contributes to the loss of muscle mass, but the mechanisms underlying this process are largely unknown. Caspase-dependent as well as caspase-independent pathways have been implicated, and the mode by which atrophy is induced likely determines the apoptotic mechanisms that are utilized. It remains to be determined whether a decrease in apoptosis will alleviate atrophy and distinct research strategies may be required to clarify the different causes of skeletal muscle mass loss. In this review, it was also speculated that apoptosis is a normal regulatory process that the myofiber can use to reduce the number of nuclear domains, thus ensuring optimal cell functions according to the mechanical load imposed on the muscle. ©FUNPEC-RP.